The development and provision of educational services for children with intellectual disabilities in Egypt - Abdelhameed,Hala (2010)
This paper aims to provide an overview of the development and provision of educational services for children with intellectual disabilities in Egypt. Intellectual disability is a significant sub-average general intellectual functioning existing concurrently with deficits in adaptive behaviour and manifested during the developmental period. The education of children with intellectual disabilities is a right endowed and authorised by the Egyptian government. The Ministry of Education in Egypt is keen to provide those children who have intellectual disabilities, along with other children with special needs, with an appropriate education that addresses their needs and allows them to live in society using their full potential, as typically developing children. Observations and interviews were carried out to collect further information about the educational services the children with intellectual disabilities receive in Egypt. The findings of this study indicated that, despite the efforts exerted by the Ministry of Education, to provide advanced and new services for children with intellectual disabilities, the provision may still need improvements. A series of recommendations was suggested to improve the services that children with intellectual disabilities receive in Egypt.